Age and structural evolution of the orogenic gold deposits in Kullaa, SW Finland: Implications for fluid activity and gold precipitation during evolving orogeny - Kara, Jaakko; Manninen, Jukka; Skyttä, Pietari; Väisänen, Markku; O'Brien, Hugh; Cutts, Kathryn; Nikkola, Paavo (Elsevier, 2025)
We have studied two gold deposits, Välimäki and Kultakallio, located in SW Finland, to understand the interplay between gold precipitation, fluid activity and structural evolution within the Paleoproterozoic Svecofennian orogen. The Välimäki deposit is hosted by paragneisses characterised by pervasive silicification and the occurrence of foliation parallel quartz veins. The Kultakallio garnet-bearing gabbro shows two generations of quartz veins associated with arsenopyrite and graphite. Zircons from the leucosome within Välimäki yield an age of 1887 ± 4 Ma interpreted as the first metamorphic event (M1) associated with partial melting. In contrast, monazites of the same sample give bimodal ages at 1817 ± 7 Ma and 1794 ± 5 Ma both reflecting hydrothermal activity. In-situ zircon dating in Kultakallio yielded three age peaks at 1885 ± 4 Ma, 1859 ± 5 Ma and 1805 ± 7 Ma interpreted to represent magmatism, a secondary metamorphic event (M2) and hydrothermal activity, respectively. In-situ dating of Kultakallio titanites gives an age of 1786 ± 58 Ma and garnet an age of 1809 ± 470 Ma, which reflect the timing of the fluid activity. Based on hydrothermal ages, gold mineralising events at (I) 1815–1805 Ma and (II) 1795–1785 Ma are recognised in the study area. Stage I is related to the injection of foliation-parallel quartz veins and precipitation of arsenopyrite in which gold occurs as inclusions. Stage II is characterised by precipitation of gold associated with Te- and Bi-minerals, abundant graphite, remobilisation of pyrite and breakdown of arsenopyrite within the brittle-ductile transition zone. The NW-SE −oriented transpressional setting formed the NE-SW −oriented gold critical structures originally at 1.89–1.88 Ga (D2), which were later reactivated in the 1.83–1.78 Ga WNW-ESE transpressional setting (D3). The NW-SE trending crustal scale shear zones are suggested to act as first order structures whereas the NE-SW oriented strike-slip structures form the second order setting. In the target scale, foliation parallel and intersecting quartz veins and narrow shear zones represent the third order structures hosting the mineralisations. We suggest the driver for the fluid activity at ca. 1.80 Ga is lower crustal delamination during crustal extension in a tectonic switching cycle.